Comparing time use in mothers with autistic child and mothers with healthy child - Maryam Mohammadpour; Mehdi Rassafiani; Mina Ahmadi Kahjugh; Fatemeh Behnia; Hojjat Allah Haghgoo; Akbar Biglarian (Vesnu Publications, 2014)
Introduction: Rehabilitation and medical professionals knowledge of time use of mothers with autistic child, can help mother and family health promotion. Studies have shown that care of children with disability are generally the mother responsibility and appropriate mothers' performance are related to the well balanced use of time. So, in this study, we investigated time use of mothers with autistic child. Methods and materials: In a cross sectional study, 42 mothers with autistic children were recruited through convenient sampling. 42mothers with healthy children were also recruited and matched with these mothers as control group. Demographic questionnaire, Gilliam Autism Rating Scale (GARS- II)  and Mother Time use Questionnaire (MTUQ) were used to collect data. The data analyses were done by independent T- test and Chi- square in SPSS17. Results: Mothers with autistic child, in comparison  with mothers with healthy children, spend more time in child related task during the day (P = 0/000)but no significant differences were found in areas of self care, rest/ sleep, leisure, home work, work/ job and social participation(P > 0/05). Furthermore, quality (P = 0/006) and enjoyment (P = 0/03) of daily activities were significantly lower in mothers with autistic child compared to mothers healthy children. Percieved level of Importance related to daily activities(P = 0/23)and satisfaction of time management skills (P = 0/16), had no significant differences in both groups mothers. Conclusion: Being autistic child causes imbalance in activity areas and influences the quality aspects of time use. Key words: Autism, disability,children,mothers time use.